Marine War-risk Insurance. Hearing on H.R. 6554, a Bill to Amend War-risk Insurance Provisions of the Merchant Marine Act, 1936, as Amended, in Order to Expedite Ocean Transportation and Assist the War Effort. (U.S. Congressional Research., 1942)
Committee print.